(3OSJhQ WHjs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hHYO MeO Gddg JYGdj aChd eG jLH Ydi GdWHjH Cf jHJOj Hg gh eYQaI GdYdI HLfSgG hfhYgG hebOGQgG ai fhYgG s
(3BNQgG (B:s
(3agPG eG YfO ef GdHOjfj jbGHd HGdcJH GdeUfaI ai gPG GdHGH hEf JWGHbJ GdTgGOGJ Hg Ydjg GSJYedJ s
(3Vef eLehY , JQJjHgG (B: 17s
(3hgh efbhd ef cdGeg ai GdWHs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs